Professional Competence and Learning Communities: Effects on Teaching Quality in Indonesian Elementary Schools - Baroroh, Umi; Bunyamin; Sudana, I Made (Papanda Publisher, 2025)
Indonesian elementary education continues to face persistent challenges in achieving high-quality learning outcomes, particularly amid the ongoing implementation of the Merdeka Curriculum. A critical issue lies in the limited empirical understanding of how teachers’ professional competence and participation in learning communities interact to influence teaching quality. This study aims to examine the effects of professional competence and learning communities on the quality of learning among public elementary school teachers in Ngaliyan District, Semarang City. Using a quantitative explanatory design, data were collected from 188 teachers through validated questionnaires that measured dimensions of professional competence, involvement in learning communities, and indicators of learning quality. Statistical analyses, including simple and multiple linear regression, revealed that both professional competence and learning communities have significant positive effects on learning quality. Learning communities showed a stronger individual contribution (R² = 0.616) compared to professional competence alone (R² = 0.291), and together they explained 65.9% of the variance in learning quality. These findings highlight the importance of not only enhancing individual teacher competencies but also fostering collaborative professional cultures in schools. The study suggests that educational policies and professional development programs should emphasize the establishment of effective learning communities alongside traditional competency-based training. This integrated approach is essential to support the successful implementation of curriculum reforms and improve educational outcomes in Indonesian elementary schools.